Brace for impact! COVID-19, lockdown and the initial reaction and adaptability of Flemish travel consumers - Marco Scholtz; Kaat De Ridder (Journal of Tourism, Heritage & Services Marketing, 2021)
Purpose: To determine the influence of COVID-19 and the first 2020 lockdown on Flemish people's initial travel behaviour perceptions, a hypothetical scenario was posed to respondents where they were asked to keep in mind a situation where they might be able to travel again during the summer of 2020 (July/August). This research had two main aims: i) the pre-lockdown travel plans for summer 2020 were determined; ii) the extent to which respondents would adapt their travel behaviour if they were hypothetically allowed to travel again by summer 2020. Methods: This exploratory research was done by means of an online quantitative questionnaire of which 1803(n) complete responses were obtained through convenience and snowball sampling. Results: The results revealed that respondents did have initial travel plans for the 2020 summer (July/August) period, but that they adjusted their planning to mostly travelling nationally/locally, potentially benefitting the local tourism industry. These findings (i) indicate the importance of directing marketing efforts towards the local travel market and (ii) contribute to literature regarding the resilience of the (local) tourism industry. Additionally, the research unveils how the industry should do long-term planning by taking the immediate travel behaviour changes of the Flemish travel consumers into account through regular intervals of consumer research so that it can pick up on possible behavioural trends and ready itself. Implications: Government, together with the industry, can work towards policies that act as a safety net during possible future industry disasters to minimize the negative impacts and foster a swift recovery.
Keywords: L10; R41; D18; 330; coronavirus; epidemic; lockdown; travel behaviour; tourism